Kinetic Treatments for Catalyst Activation and Deactivation Processes based on Variable Time Normalization Analysis. (7th June 2019) - Martínez‐Carrión, Alicia; Howlett, Michael G.; Alamillo‐Ferrer, Carla; Clayton, Adam D.; Bourne, Richard A.; Codina, Anna; Vidal‐Ferran, Anton; Adams, Ralph W.; Burés, Jordi
Abstract: Progress reaction profiles are affected by both catalyst activation and deactivation processes occurring alongside the main reaction. These processes complicate the kinetic analysis of reactions, often directing researchers toward incorrect conclusions. We report the application of two kinetic treatments, based on variable time normalization analysis, to reactions involving catalyst activation and deactivation processes. The first kinetic treatment allows the removal of induction periods or the effect of rate perturbations associated with catalyst deactivation from kinetic profiles when the quantity of active catalyst can be measured. The second treatment allows the estimation of the activation or deactivation profile of the catalyst when the order of the reactants for the main reaction is known. Both treatments facilitate kinetic analysis of reactions suffering catalyst activation or deactivation processes. Abstract : Mit der Zeit gehen : Zwei verschiedene kinetische Analysemethoden auf Basis der zeitvarianten Normierungsanalyse (VTNA) werden für die Untersuchung von Reaktionen mit Katalysator‐Desaktivierungsprozessen und ‐Aktivierungsprozessen beschrieben. Die studierten Fälle sind eine von einem supramolekularen Rh‐Komplex katalysierte Hydroformylierung und eine aminokatalytische Michael‐Reaktion.